2014
DOI: 10.1007/s00442-014-3153-x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 alters community composition and response to nutrient enrichment of freshwater phytoplankton

Abstract: Nutrients can limit the productivity of ecosystems and control the composition of the communities of organisms that inhabit them. Humans are causing atmospheric CO2 concentrations to reach levels higher than those of the past millions of years while at the same time propagating eutrophication through the addition of nutrients to lakes and rivers. We studied the effect of elevated CO2 concentrations, nutrient addition and their interaction in a series of freshwater mesocosm experiments using a factorial design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 64 publications
2
41
3
Order By: Relevance
“…, Low‐Decarie et al. ), as well as on intrinsic ecophysiological characteristics. Species which are able to use HCO 3 − in addition to CO 2 will be at an advantage at high pH by being less dependent on CO 2 availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Low‐Decarie et al. ), as well as on intrinsic ecophysiological characteristics. Species which are able to use HCO 3 − in addition to CO 2 will be at an advantage at high pH by being less dependent on CO 2 availability.…”
Section: Discussionmentioning
confidence: 99%
“…) and increase in phytoplankton biomass (Low‐Decarie et al. ). Although if lake concentrations of CO 2 are determined by the catchment (Maberly et al.…”
mentioning
confidence: 99%
“…0.5, no detectable salinity 0.00 ppt, conductivity 80.9 + s.d. 9.1 mS cm 21 [15]). Our ABRs were set up to enrich for microalgae through the provision of light (continuous approx.…”
Section: Materials and Methods (A) Enrichment Using An Amplifying Biormentioning
confidence: 99%
“…), and recent experimental work (Low‐Decarie et al . , ) and paleolimnological reconstructions (Wolfe & Siver ) have suggested that phytoplankton community composition may vary along CO 2 concentration gradients (Low‐Decarie et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…; Low‐Decarie et al . , , ; Jansson et al . ) work has suggested that increases in ambient CO 2 relative to current atmospheric equilibrium could influence algal performance and therefore whole ecosystem primary production (Urabe et al .…”
Section: Introductionmentioning
confidence: 99%